Association of Gestational Weight Gain With Maternal and Infant Outcomes: A Systematic Review and Meta-Analysis. Issue 2 (June 2018) - Goldstein, R.F.; Abell, S.K.; Ranasinha, S.; Misso, M.; Boyle, J.A.; Black, M.H.; Li, N.; Hu, G.; Corrado, F.; Rode, L.; Kim, Y.J.; Haugen, M.; et al.
Abstract : ( JAMA. 2017;317:2207–2225) Excessive and insufficient gestational weight gain have been associated with a variety of adverse maternal and neonatal outcomes. The Institute of Medicine (IOM) has guidelines for gestational weight gain that recommend less weight gain for women with greater body mass index. However, evidence regarding the association between pregnancy outcomes and recommended weight gain based on the IOM guidelines is limited. This systematic review and meta-analysis was performed to investigate the association between gestational weight gain above and below the IOM guidelines and maternal and infant outcomes.